Domestikasi Ruang dalam Durga Umayi: Melampaui Nation, Menuju “Tubuh Politis” - Achmad Fawaid (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
This paper aim to show the "spatial politics" strategy done by Mangunwijaya in Durga Umayi (1991). Spatiality was formed through the character of a female figure, Iin Sulinda Pertiwi Nusamusbida, who continuously created tension and contestation towards the 'ideal home' (place) imagined by the state. Mangunwijaya deconstructed and dominated places by offering scale reversal and exceeding the idea (geographical) of the nation through magical realism, domestic space, travel, and the body.